Evaluasi Kebijakan Penilaian TKDN dalam Skema Penghitungan Berbasis Pengembangan Inovasi pada Perangkat Telepon Seluler - Al Araf Assadallah Marzuki; Mosgan Situmorang (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2024)
Article 35 of Minister of Industry Regulation No. 29 of 2017 states that besides manufacturing aspects, the calculation of Domestic Component Level (TKDN) for mobile devices may utilize an innovation-based calculation scheme. However, this policy is deemed biased as it only benefits large companies selling products without assembly in Indonesia, while their competitors have invested in local production infrastructure to fulfill TKDN obligations. This study aims to evaluate the TKDN Assessment Policy in the innovation-based calculation scheme. The research problem is whether this policy aligns with TKDN policies in Law No. 3 of 2014 concerning Industry. This research employs a normative legal approach, focusing on literature review and legislative analysis. Findings indicate that the TKDN regulation in the innovation-based calculation scheme provides flexibility for companies to meet TKDN standards more flexibly but also raises concerns about decreasing use of local components, contradicting the spirit of Law No. 3 of 2014, which promotes the use of domestic products to fulfill TKDN. Therefore, a thorough evaluation of the TKDN regulation in the innovation-based calculation scheme is needed to maintain the balance of the domestic industry.